Fluidity and mobility of the pilgrimage place: Medjugorje in pilgrimage objects - Belaj, Marijana; Kelemen, Petra (2013)
Taking ethnography of pilgrimage practices in Medjugorje as a starting point, the authors indicate the processes of sacralization of everyday life and desacralization of the pilgrimage place. They discuss the fluidity of boundaries and mobility of the pilgrimage place. Many anthropologists of pilgrimage locate the pilgrimage place outside the temporal and spatial boundaries of everyday life or at least at its margins. Moreover, they believe that traveling outside one's own home culture is the defining characteristic of the development of pilgrimage. In the paper the authors explore whether the separation between the pilgrimage place and everyday reality is indeed clear and defined. The focus is on the objects brought to and from Medjugorje. By bringing a variety of personal objects to Medjugorje, pilgrims inscribe their everyday issues in the pilgrimage place, simultaneously constructing Medjugorje as a pilgrimage center. On the other hand, the taking of objects from the pilgrimage place as mementos or gifts for one's loved ones turns the place into a part of everyday symbolic inventory, even for people who have never visited it. Coming from a powerful pilgrimage place, these objects are often attributed with powers for solving everyday crises. The processes of sacralization of the everyday (mementos and gifts from the pilgrimage place) and desacralization of the pilgrimage place (personal objects reflecting pleas and hopes relating to everyday issues) blur the supposedly clear boundary between everyday reality ("common", "profane", "this-worldly") and the separate reality of the pilgrimage place ("extraordinary", "sacred", "otherworldly"). The authors conclude that, although Medjugorje has a fixed geographical position, the space of this pilgrimage place is as wide as the space of existence of its users.
ENG